2020
DOI: 10.1109/access.2020.2991959
|View full text |Cite
|
Sign up to set email alerts
|

SyntheticNET: A 3GPP Compliant Simulator for AI Enabled 5G and Beyond

Abstract: The rapid evolution of cellular system design towards 5G and beyond gives rise to a need for investigation of the new features, design proposals and solutions in realistic settings for various deployments and use case scenarios. While many system level simulators for 4G and 5G exist today, there is particularly a dire need for a 3GPP compliant system level holistic and realistic simulator that can support evaluation of the plethora of AI based network automation solutions being proposed in literature. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Labeled 3 in the figure is the main equipment composed of SDRs and 3GPP compliant software to act as the base station. To connect it to the Internet and other base stations via fiber, a fiberethernet switch is exploited as shown in 4 . The SDRs of the callbox are connected to the amplifiers using SMA cables.…”
Section: B Network Design and Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeled 3 in the figure is the main equipment composed of SDRs and 3GPP compliant software to act as the base station. To connect it to the Internet and other base stations via fiber, a fiberethernet switch is exploited as shown in 4 . The SDRs of the callbox are connected to the amplifiers using SMA cables.…”
Section: B Network Design and Planningmentioning
confidence: 99%
“…Many network simulators have been developed to overcome the limits of analytical modeling methods. However, most of the existing simulators lack complete system realization or may require excessive computational power [4]. Meanwhile, the more practical cellular network experimentation in the form of field trials is reserved exclusively for the network operators with large research and development (R&D) funds as conducting field trials on a large scale is time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the futuristic vision of 6G network design has been stepping forth based on the amalgamation of trending ICT and data technology in tandem with the cloud-native computing model to the 5G core network, increasing the prospects of new services. [132], [133]. New features and enablers expected from B5G/6G networks for industrial DT are identified and summarized in Fig.…”
Section: G-and-beyond/6g Network and Aoi-aware Green Communicationmentioning
confidence: 99%
“…In [10], the authors have evaluated the performance of Simul5G, a 5G emulator which introduces lightweight models of UEs and gNBs, facilitating the simulation of large-scale 5G multicellular networks. In [11], the SyntheticNET simulator is introduced, based on python, incorporating the latest 3GPP 5G release as well as AI-based ray-tracing propagation modelling. The developed simulator can include additional AI/ML-based solutions for autonomous configuration and optimization of network parameters.…”
Section: Introductionmentioning
confidence: 99%